2011
DOI: 10.1111/j.1365-2125.2011.04004.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective serotonin re‐uptake inhibiting antidepressants and the risk of overanticoagulation during acenocoumarol maintenance treatment

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• Coumarin anticoagulants and selective serotonin re-uptake inhibitors (SSRIs) have been reported to cause bleeding. Combination of these drug groups might enhance this risk. Case reports showed an increase of prothrombin time for the combination of warfarin with fluvoxamine and fluoxetine. This has not yet been confirmed by population based studies. WHAT THIS STUDY ADDS• Fluvoxamine and venlafaxine increased prothrombin time in users of acenocoumarol above a critical va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…21-23 A study by Teichert et al showed that users of SSRIs were more likely to be over-anticoagulated, although our analysis found a significant association even after controlling for supratherapeutic INRs. 24 Labos et al reported that patients taking antiplatelet agents had significant increases in bleeding risk among those patients taking aspirin, clopidogrel, or both along with an SSRI when compared to their non-SSRI taking counterparts. 25 Recent evidence has suggested improved physical and psychological outcomes in patients treated with SSRIs after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…21-23 A study by Teichert et al showed that users of SSRIs were more likely to be over-anticoagulated, although our analysis found a significant association even after controlling for supratherapeutic INRs. 24 Labos et al reported that patients taking antiplatelet agents had significant increases in bleeding risk among those patients taking aspirin, clopidogrel, or both along with an SSRI when compared to their non-SSRI taking counterparts. 25 Recent evidence has suggested improved physical and psychological outcomes in patients treated with SSRIs after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…The SSRIs are among the most commonly prescribed drug classes . Fluvoxamine and fluoxetine are the two SSRIs most likely to inhibit warfarin metabolism, which is supported by several case reports.…”
Section: Specific Drug‐drug Interactions By Psychotropic Classmentioning
confidence: 82%
“…The SSRIs are among the most commonly prescribed drug classes. 70 Fluvoxamine 12, 13 and fluoxetine [14][15][16] are the two SSRIs most likely to inhibit warfarin metabolism, which is supported by several case reports. In two reports of a fluvoxamine interaction with warfarin, the INR was elevated without hemorrhagic complications, 12,13 although in one report of a fluoxetine-warfarin interaction, an elderly man experienced a fatal intracerebral hemorrhage.…”
Section: Antidepressantsmentioning
confidence: 83%